PEMBERDAYAAN PEREMPUAN DALAM MEMUTUS MATA RANTAI COVID-19 - Desy Dwi Cahyani; Rita Yulifah; Asworoningrum Yulindahwati; Lisa Purbawaning (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2021)
The COVID-19 pandemic has an impact on various sectors of life. During the COVID-19 pandemic, the suggestion to stay at home has had a positive impact on improving family communication, increasing attachment between family members, including childcare and increased ability to use. information Technology. New habitual practices that consistently make a person, family, group or community able to maintain personal health and play an active role in realizing public health in the face of the COVID-19 pandemic. The aim of this activity is Empowering Women in Breaking the Covid-19 Chain "expected by mothers. PKK has increased its knowledge, and is able to apply new habit patterns during the Covid-19 pandemic. This activity was carried out on August 26, 2020 through a zoom meeting. Evaluation of this activity was carried out by filling out a questionnaire via google form with the results that 49% of the public were satisfied with the topic, 49% of the public were satisfied with information on the topic of discussion, 52% of the public understood the resource's explanation, and 46 % The community is very satisfied with this activity. The follow-up plan of this activity is to provide other education to the community related to women's empowerment, namely the role of women in providing motivation to the community to increase knowledge about health protocols to the application stage of implementing health protocols in the community, considering that even though counseling has been carried out in various ways there are still many violations in implementing health protocols in the new normal era